Quaternary volcanic activity of the southern Red Sea: new data and assessment of models on magma sources and Afar plume-lithosphere interaction - Volker, Frank; Altherr, Rainer; Jochum, Klaus-Peter; McCulloch, Malcolm T. (Tectonophysics, 1997)
Chemical compositions and SrNdPb isotopic ratios are reported for Quaternary alkaline volcanic rocks from the southern Red Sea and adjacent regions. Samples from the Ramad seamount (17°N) have highly radiogenic Pb isotope ratios (206Pb/204Pb = 19.59-19.61) and comparatively depleted Sr and Nd signatures. In isotope diagrams the samples from this seamount fall on extensions of linear arrays defined by samples of Red Sea N-type and E-MORB and confirm the existence of an important HIMU-type component in the mantle beneath the southern Red Sea. Alkali basalts from the islands of Hanish and Zubair located in the southernmost part of the Red Sea do not lie on isotope mixing lines defined by Red Sea MORB and Ramad seamount samples. Instead, their data points are shifted towards the data field of Quaternary Afar and Yemen volcanic rocks, thus reflecting the presence of a third isotopic component with hybrid EM1-EM2 characteristics which dominates the continental volcanic rocks on both shoulders of the southernmost Red Sea. The systematic covariation of isotope ratios and geographic position in southern Red Sea volcanic rocks are very similar to those observed along the Gulf of Aden and thus support the torus plume model proposed by Schilling et al. [Schilling, J.-G., Kingsley, R.H., Hanan, B.B., McCully, B.L., 1992. NdSrPb variations along the Gulf of Aden: Evidence for Afar mantle plume-continental lithosphere interaction. J. Geophys. Res. 97, 10927-10966].